Insurgency and peace policies of the Marcos and the Aquino governments an initial inquiry - Brillantes, Alex B., Jr (Philippine Journal of Public Administration, 1988)
One of the problems which the Aquino government inherited from the past regime is insurgency. But while the Marcos regime had to deal only with the leftist insurgency represented by the NPAs and the secessionist insurgency represented by the MNLF, the new regime has to deal with an additional rightist insurgency represented by the elements from within the armed forces itself to quell the leftist and secessionist insurgencies, the Aquino government formulated policies not unlike the predecessor's. The policies were a combination of the use of the state's military force and the attempt to address the root cause of the problem which is economic underdevelopment. The Marcos regime, in its fight against the insurgents used a hardline policy and failed heavily on economic development efforts. The Aquino government, although initially marked with reconciliatory policies, has also adopted a hardline policy like the former government.